Primary trauma of female partners in a military sample: individual symptoms and relationship satisfaction - Hamilton, Stacy; Goff, Briana S. Nelson; Crow, Janet R.; Reisbig, Allison M.J. (Taylor & Francis (Routledge), 2009)
Research traditionally has focused on the development of symptoms in those who experienced war-trauma directly but overlooked the impact of trauma in the partners of soldiers. The current study reports data from 45 couples where the male partners were Army soldiers who recently returned from deployments to Iraq (Operation Iraqi Freedom) or Afghanistan (Operation Enduring Freedom). Results from this study indicated that female partner primary trauma, particularly trauma related to PTSD re-experiencing and arousal symptoms, has an influence on levels of relationship satisfaction, both for female partners and soldiers.
Keywords: Female trauma; PTSD; Military couples; Operation Iraqi Freedom; Operation Enduring Freedom; Post-traumatic stress disorder